Reliability of the Walker Cranial Nonmetric Method and Implications for Sex Estimation1. Issue 3 (6th January 2016) - Lewis, Cheyenne J.; Garvin, Heather M.
Abstract: The cranial trait scoring method presented in Buikstra and Ubelaker (Standards for data collection from human skeletal remains. Fayetteville, AR: Arkansas Archeological Survey Research Series No. 44, 1994) and Walker (Am J Phys Anthropol, 136, 2008 and 39) is the most common nonmetric cranial sex estimation method utilized by physical and forensic anthropologists. As such, the reliability and accuracy of the method is vital to ensure its validity in forensic applications. In this study, inter‐ and intra‐observer error rates for the Walker scoring method were calculated using a sample of U.S. White and Black individuals ( n = 135). Cohen's weighted kappas, intraclass correlation coefficients, and percentage agreements indicate good agreement between trials and observers for all traits except the mental eminence. Slight disagreement in scoring, however, was found to impact sex classifications, leading to lower accuracy rates than those published by Walker. Furthermore, experience does appear to impact trait scoring and sex classification. The use of revised population‐specific equations that avoid the mental eminence is highly recommended to minimize the potential for misclassifications.